Studying Some Properties of Microwave-Cured Resin After Adding PP Fibers and ZrO2 NPs (Mustansiria Dental Journal, 2024)
Aim of the study: Since the introduction of acrylic resin as a denture base material, it suffered from having unsatisfactory properties and processing method. So, the use of microwave cured technique for the acrylic as modified procedure to simplify the manipulation of laboratory procedure and reinforcing of polymer by materials such as fibers and nanoparticles can maintain good resin material and to overcome these limitations. This study was performed to evaluate the effect of adding polypropylene fibers with and without different concentration of ZrO2nanoparticles into resin on some properties such as surface hardness and roughness.Materials and methods: 100 samples were split into 2 groups depending on test type, 50 specimens were subdivided into 5 groups (control group without any reinforcement, reinforced with polypropylene fibers group alone and other three groups reinforced acrylic with polypropylene fibers with 0.5%,1%,1.5%ZrO2 respectively).Results: The results of polypropylene fibers addition into acrylic revealed a non-significant for both tests. The addition polypropylene fibers with ZrO2 nanoparticles showed significant heightening in the hardness and significant decrease in surface roughness.Conclusion: The conclusion of this study was both ZrO2nanoparticles with polypropylene fibers addition into resin improved the surface hardness with reduction in the surface roughness of acrylic resin.